Exploring Patterns of COPD Exacerbations and Comorbid Flare-Ups - van Dijk SH; Brusse-Keizer MG; Effing T; van der Valk PD; Ploumen EH; van der Palen J; Doggen CJ; Lenferink A (International Journal of COPD, 2023)
Sanne HB van Dijk,1,2 Marjolein GJ Brusse-Keizer,1,3 Tanja Effing,4,5 Paul DLPM van der Valk,2 Eline H Ploumen,1,6 Job van der Palen,3,7 Carine JM Doggen,1,8 Anke Lenferink1,2,8 1Health Technology & Services Research, TechMed Centre, University of Twente, Enschede, the Netherlands; 2Department of Pulmonary Medicine, Medisch Spectrum Twente, Enschede, the Netherlands; 3Medical School Twente, Medisch Spectrum Twente, Enschede, the Netherlands; 4College of Medicine and Public Health, School of Medicine, Flinders University, Adelaide, Australia; 5School of Psychology, Faculty of Health and Medical Sciences, University of Adelaide, Adelaide, Australia; 6Department of Cardiology, Medisch Spectrum Twente, Enschede, the Netherlands; 7Cognition, Data & Education, BMS Faculty, University of Twente, Enschede, the Netherlands; 8Clinical Research Centre, Rijnstate Hospital, Arnhem, the NetherlandsCorrespondence: Anke Lenferink, Tel +31 534896311, Email a.lenferink@utwente.nlBackground: Comorbidities are known to complicate disease management in patients with Chronic Obstructive Pulmonary Disease (COPD). This is partly due to lack of insight into the interplay of acute exacerbations of COPD (AECOPD) and comorbid flare-ups. This study aimed to explore patterns of AECOPDs and comorbid flare-ups.Methods: Data of increased symptoms were extracted from a 12-month daily symptom follow-up database including patients with COPD and comorbidities (chronic heart failure (CHF), anxiety, depression) and transformed to visualizations of AECOPDs and comorbid flare-up patterns over time. Patterns were subsequently categorized using an inductive approach, based on both predominance (ie, which occurs most often) of AECOPDs or comorbid flare-ups, and their simultaneous (ie, simultaneous start in ≥ 50%) occurrence.Results: We included 48 COPD patients (68 ± 9 years; comorbid CHF: 52%, anxiety: 40%, depression: 38%). In 25 patients with AECOPDs and CHF flare-ups, the following patterns were identified: AECOPDs predominant (n = 14), CHF flare-ups predominant (n = 5), AECOPDs nor CHF flare-ups predominant (n = 6). Of the 24 patients with AECOPDs and anxiety and/or depression flare-ups, anxiety and depression flare-ups occurred simultaneously in 15 patients. In 9 of these 24 patients, anxiety or depression flare-ups were observed independently from each other. In 31 of the included 48 patients, AECOPDs and comorbid flare-ups occurred mostly simultaneously.Conclusion: Patients with COPD and common comorbidities show a variety of patterns of AECOPDs and comorbid flare-ups. Some patients, however, show repetitive patterns that could potentially be used to improve personalized disease management, if recognized.Keywords: chronic obstructive pulmonary disease, heart failure, anxiety, depression, personalized medicine, disease monitoring